2003
DOI: 10.1046/j.1464-5491.2003.00957.x
|View full text |Cite
|
Sign up to set email alerts
|

The association between satisfaction with services provided in primary care and outcomes in Type 2 diabetes mellitus

Abstract: The findings from this study demonstrate that there is an association between satisfaction and outcome in diabetes, which goes across all the GPAS domains. This suggests that processes that can act to increase patient satisfaction may be contributing to improved clinical outcomes. More development work is needed in this field to explore and elucidate the complex relationship between satisfaction and clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
131
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(137 citation statements)
references
References 40 publications
2
131
0
4
Order By: Relevance
“…15,16 The results from the trial reported here have shown that point-of-care testing was not only acceptable but led to positive outcomes in terms of patient medication adherence 17 and improved therapeutic control, 3 providing evidence that point-of-care testing in the general practice setting can be used as an effective alternative to pathology laboratory testing.…”
Section: Implications For Future Research and Clinical Practicementioning
confidence: 94%
“…15,16 The results from the trial reported here have shown that point-of-care testing was not only acceptable but led to positive outcomes in terms of patient medication adherence 17 and improved therapeutic control, 3 providing evidence that point-of-care testing in the general practice setting can be used as an effective alternative to pathology laboratory testing.…”
Section: Implications For Future Research and Clinical Practicementioning
confidence: 94%
“…At the same time, studies show that care organized around a primary care relationship results in better outcomes at lower cost. [79][80][81][82] Incentives can be developed that will allow Americans to choose the kind of health care they want, but at a price that refl ects the effectiveness and effi ciency of the model they choose. Individuals should be able to choose or change their medical home through an easy and well-defi ned process.…”
Section: Strategic Prioritiesmentioning
confidence: 99%
“…Kuo labiau ligonis patenkintas suteikiama pagalba, tuo geresnė jo emocinė būklė, kuri, savo ruožtu, sąlygoja geresnę fizinę sveikatą, ligos eigą, retesnes komplikacijas ir pan. (Glasgow, Toobert, 1988;Alazri, Neal, 2003).…”
Section: įVadasunclassified